Balloon Test Occlusion of Internal Carotid Artery in Recurrent Nasopharyngeal Carcinoma Before Endoscopic Nasopharyngectomy: A Single Center Experience - Yang, Renhao; Wu, Hui; Chen, Binghong; Sun, Wenhua; Hu, Xiang; Wang, Tianwei; Guo, Yubin; Qiu, Yongming; Dai, Jiong (Frontiers in Oncology, 2021)
Objectives Endoscopic nasopharyngectomy (ENPG) is a promising way in treating recurrent nasopharyngeal carcinoma (rNPC), but sometimes may require therapeutic internal carotid artery (ICA) occlusion beforehand. Balloon test occlusion (BTO) is performed to evaluate cerebral ischemic tolerance for ICA sacrifice. However, absence of neurological deficits during BTO does not preclude occur of delayed cerebral ischemia after permanent ICA occlusion. In this study, we evaluate the utility of near-infrared spectroscopy (NIRS) regional cerebral oxygen saturation (rSO2) monitoring during ICA BTO to quantify cerebral ischemic tolerance and to identify the valid cut-off values for safe carotid artery occlusion. This study also aims to find out angiographic findings of cerebral collateral circulation to predict ICA BTO results simultaneously. Material and Methods 87 BTO of ICA were performed from November 2018 to November 2020 at authors’ institution. 79 angiographies of collateral flow were performed in time during BTO and classified into several Subgroups and Types according to their anatomic and collateral flow configurations. 62 of 87 cases accepted monitoring of cerebral rSO2. Categorical variables were compared by using Fisher exact tests and Mann–Whitney U tests. Receiver operating characteristic curve analysis was used to determine the most suitable cut-off value. Results The most suitable cut-off △rSO2 value for detecting BTO-positive group obtained through ROC curve analysis was 5% (sensitivity: 100%, specificity: 86%). NIRS rSO2 monitoring wasn’t able to detect BTO false‐negative results (p = 0.310). The anterior Circle was functionally much more important than the posterior Circle among the primary collateral pathways. The presence of secondary collateral pathways was considered as a sign of deteriorated cerebral hemodynamic condition during ICA BTO. In Types 5 and 6, reverse blood flow to the ICA during BTO protected patients from delayed cerebral ischemia after therapeutic ICA occlusion (p = 0.0357). In Subgroup IV, absence of the posterior Circle was significantly associated with BTO-positive results (p = 0.0426). Conclusion Angiography of cerebral collateral circulation during ICA BTO is significantly correlated with ICA BTO results. Angiographic ICA BTO can be performed in conjunction with NIRS cerebral oximeter for its advantage of being noninvasive, real-time, cost-effective, simple for operation and most importantly for its correct prediction of most rSO2 outcomes of ICA sacrifice. However, in order to ensure a safe carotid artery occlusion, more quantitative adjunctive blood flow measurements are recommended when angiography of cerebral collateral circulation doesn’t fully support rSO2 outcome among clinically ICA BTO-negative cases.